SIFAT FISIKA DAN KIMIAWI KOMPONEN ASAP CAIR TEMPURUNG KELAPA HASIL ADSORPSI PADA ARANG AKTIF - Syahraeni Kadir; Purnama Darmadji Darmadji; Chusnul Hidayat; Supriyadi Supriyadi (Universitas Tadulako, 2014)
Characterization of physical and chemical properties of aroma compounds from liquid smoke is a challenge because there is no satisfactory method of separation due to compound contributors generally present in a matrix at very low concentrations. This study aimed to separate and identify the components of